The roles of ICT in driverless, automated railway operations. Issue 4 (1st January 2013) - Narayanaswami, Sundaravalli; Mohan, Shiv
Transportation plays an important role in building supply chains; several emerging theories and practices of supply chain management rely heavily on transportation. In recent years, ICT has been favourably employed in engineering, operations and business sectors. However applications and opportunities of ICT are still evolving; with reference to ICT, today's norm is obsolete tomorrow. Rail transport too is becoming increasingly dependent on ICT, not only for commercial purposes such as asset management, passenger ticketing and information broadcasting etc., but also for mission/safety-critical functions, particularly in infrastructure development in the era of high speed and automated railways. A critical issue is that railway infrastructure is capital intensive and has a long gestation period. The initial effort and cost of developing ICT for safety/mission critical railway applications are high and detailed planning is necessary to study requirements and product specifications. The ever evolving ICT standards contribute to high cost over-runs and long lead time. Whilst the rail industry has embraced the technology of the day, several ICT advancements remain unexplored by railways; financial and technical mishaps tend to make one cautious. This paper analyses automated rail operational technology in-depth and the role of ICT in a broader overview of enhancing transportation capacity.